(untitled) - Maniktala, Sanjaya (Amsterdam, 2006)
Sanjaya does a monthly column for me, and I am a jump-up-and-cheer! fan of his work. He is one of those few engineers who can give you the intensive math-based theory of power supply design and component selection, practical tips and techniques based years of hands on experience in many countries around the world (even what brand of solder to use), and entertaining anecdotes and personal observations -- all in the same readable, well-illustrated package.
Keywords: Switching power supplies,Sự đảo mạch nguồn cung cấp điện